2019
DOI: 10.1002/jctb.6284
|View full text |Cite
|
Sign up to set email alerts
|

Organic phase screening for in‐stream reactive extraction of bio‐based 3‐hydroxypropionic acid: biocompatibility and extraction performances

Abstract: BACKGROUND 3‐Hydroxypropionic acid (3‐HP) production through glycerol bioconversion by Lactobacillus reuteri suffers from low yields and productivities due to product inhibition. Reactive extraction assisted by a Hollow Fibre Membrane Contactor (HFMC) is a promising strategy for process intensification. However, the use of this integrated system is hindered by extraction phase toxicity towards the microorganism. This study describes a solvent selection strategy based on extraction performance (extraction yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
(151 reference statements)
0
7
0
Order By: Relevance
“…Figure A presents that mixtures of 2-phenylethanol with methyl isobutyl ketone and 2-methyl-3-buten-2-ol have the more negative excess volumes, and Figure B shows that these solvents have lower viscosities than 2-phenylethanol. These characteristics indicate that these solvents could be good extracting agents for ISPR of 2-phenylethanol from fermentation broth in terms of their volumetric and transport properties. , Moreover, methyl isobutyl ketone and 2-methyl-3-buten-2-ol are categorized as ”recommended” based on CHEM21 methodology (Table ) because they have flash points higher than 333.15 K, boiling points between 343.15 K and 412.15 K, and according to GHS, do not have any significant risk . Also, methyl isobutyl ketone is relatively inexpensive and is cataloged as recommended for green processes based on the list published by Esteban et al The biggest challenge for the incorporation of the solvents in an ISPR is related to the biocompatibility or low-toxicity on the yeast, , so further studies are required for understanding the yeast–solvent behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure A presents that mixtures of 2-phenylethanol with methyl isobutyl ketone and 2-methyl-3-buten-2-ol have the more negative excess volumes, and Figure B shows that these solvents have lower viscosities than 2-phenylethanol. These characteristics indicate that these solvents could be good extracting agents for ISPR of 2-phenylethanol from fermentation broth in terms of their volumetric and transport properties. , Moreover, methyl isobutyl ketone and 2-methyl-3-buten-2-ol are categorized as ”recommended” based on CHEM21 methodology (Table ) because they have flash points higher than 333.15 K, boiling points between 343.15 K and 412.15 K, and according to GHS, do not have any significant risk . Also, methyl isobutyl ketone is relatively inexpensive and is cataloged as recommended for green processes based on the list published by Esteban et al The biggest challenge for the incorporation of the solvents in an ISPR is related to the biocompatibility or low-toxicity on the yeast, , so further studies are required for understanding the yeast–solvent behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Also, methyl isobutyl ketone is relatively inexpensive and is cataloged as recommended for green processes based on the list published by Esteban et al The biggest challenge for the incorporation of the solvents in an ISPR is related to the biocompatibility or low-toxicity on the yeast, , so further studies are required for understanding the yeast–solvent behavior. Nevertheless, these problems might be overcome by using coupled liquid–liquid extraction with membrane systems to avoid direct contact between the microorganisms and solvents in the case of the lack of biocompatibility. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main drawback of reactive liquid-liquid extraction as ISPR technique remains the toxicity of the extraction phases in close contact with culture media. Recently, several studies have been published on the screening and formulation of organic phases accounting for the biocompatibility with some bacteria of the genus Lactobacillus [15,16]. In spite of the identification of more biocompatible organic phases, most experimental and equilibrium modeling studies so far focused on trioctylamine (TOA)…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this work is thus to propose an equilibrium model of the extraction of 3-hydroxypropionic acid using a new formulation of organic phase that has been identified from literature to be more biocompatible than other organic phases employed for 3-HP extraction [15,17]. Among promising biocompatible organic phases, we chose to focus on N,N-didodecylmethylamine (DDMA) diluted in a mixture of 1-dodecanol and dodecane as active and inactive diluent, respectively, according to the recent study of Sánchez-Castañeda et al [15]. The authors found that DDMA showed better performances than TOA in terms of distribution coefficient as well as biocompatibility towards the natural 3-HP producer microorganism Lactobacillus reuteri.…”
Section: Introductionmentioning
confidence: 99%